PERANCANGAN RAK SEPATU DENGAN SISTEM MODULAR UNTUK MENUNJANG FASILITAS PENYIMPANAN DI RUANG TERBATAS - Andrianto, Andrianto (Waca Cipta Ruang, 2022)
The existing limited space as a result of high demand for current development needs is not in line with the design of facilities that can adapt to these conditions. One of them is footwear storage facilities, the current condition of shoe racks generally takes up a lot of space or space and the varying sizes make storage ineffective and efficient which leads to user discomfort. For this reason, it is necessary to design a shoe rack with a modular concept that can adjust so as to reduce the use of excess furniture. A modular shoe rack is a tool that functions as an organizer for storing footwear in an area or building effectively and efficiently. With modular features, this storage area can be easily disassembled for configuration needs and sizes to easily adjust to their needs. The research approach uses qualitative methods based on field findings by analyzing space production, starting with direct observations and interviews with users in limited housing as initial data and formulating problems, then developing based on literature related to functions as a design needs analysis. The result of the design is a shoe rack with a modular system that emphasizes the function aspect to match the needs of storage facilities in a limited space to make it easier for users in terms of storage, arrangement, and retrieval so that activities can run more effectively and efficiently. This design is also expected to be a reference for designs with similar designs and themes in order to increase the users effectiveness and spaces efficiency.